Semiotic analysis of the symbolic world of the Korkyt Ata complex (Journal of Philosophy Culture and Political Science, 2018)
The purpose of this article is to define the cultural and spiritual worldview of the Turkic peoples, the Korkyt Ata complex, that representing symbolic significance on the basis of semiotic analysis. Using Western research as a role model, we tried to reveal the cultural meaning of the symbolism, typical for the Kazakh society in its ethnocultural context. By disclosing the socio-cultural nature and philosophical essence, to determine the role and significance of the complex, relying on the methodological, symbolic basis for the analysis of symbolic elements, also a need to ascertain the added value of the world-class complex Korkyt Ata in the formation of the ancient Turkic civilization and the interpretation of cultural and symbolic significance was given the definition of the symbolic characteristics of the spiritual and worldview background of the memorial complex and its semiotic analysis has been done from the general complex view in the pursuit of the above-mentioned purpose.Key words: Korkyt Ata, semiotica, culture value, symbol, complex.